Hubungan antara Konsumsi Kopi dengan Gejala Gastroesophageal Reflux Disease (GERD) - Alika Putri Saraswati; Efyluk Garianto; Mulyarjo (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2021)
Introduction: Gastroesophageal Reflux Disease (GERD) is a condition that develops when there is the retrograde flow of gastric contents causing some symptoms or complications. One of the risk factors for GERD is the habit of consuming coffee, which has become a trend in everyday life without realizing it. Purpose: The purpose of this study was to determine the relationship between coffee consumption and symptoms of GERD. Method: This research is an analytic observational study using a cross-sectional study design with a sample size of 86 people. Results: The results showed that most respondents were women with a total of 66 people (73.3%). Of the 86 respondents, 55 people (64%) had coffee consumption habits and 31 people (36%) did not. Respondents who did not have the possibility of suffering from GERD were 74 people (86.0%) and those who had the possibility of suffering GERD were 12 people (14.0%). Data analysis using the Spearman correlation test showed no significant relationship (p = 0.428) between the frequency of coffee consumption and symptoms of GERD. Of the 55 respondents who consumed coffee, 12 respondents (21.8%) consumed ready-to-drink liquid coffee, 19 respondents (34.5%) consumed ground instant coffee, and 24 respondents (43.6%) consumed ground/brewed coffee. Discussion: Data analysis using the Spearman correlation test showed no significant relationship (p = 0.193) between the type of coffee consumed and the symptoms of GERD. The conclusion of this study is that there is no significant relationship between coffee consumption and GERD symptoms in students of the Faculty of Medicine, University of Hang Tuah Surabaya, class 2016-2018.